1984
DOI: 10.1136/bmj.288.6413.283-a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of digoxin and vitamin E in preventing cardiac damage caused by doxorubicin in acute myeloid leukaemia.

Abstract: The amount of fat in human milk is influenced by diurnal variations in fat content, by the stage of lactation, and, more importantly, by the method of milk collection-namely, whether it is expressed or dripped.' In human milk banks milk is usually pooled, and pooling is generally assumed to result in a more uniform fat content. We compared the fat contents in pooled banked human milk and a commercially available formula milk. We also analysed the fatty acid composition of pooled banked human milk and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Another study reported significantly decreased oral mucositis the vitamin E group 48. All other reports of toxicities found no significant differences in general toxicities between the 2 groups 48–51…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study reported significantly decreased oral mucositis the vitamin E group 48. All other reports of toxicities found no significant differences in general toxicities between the 2 groups 48–51…”
Section: Resultsmentioning
confidence: 91%
“…Of note, the study of the lowest quality was the only study to not report a statistically significant decrease in toxicity. This study by Whittaker recruited 63 patients, but only 25 (7 on vitamin E) survived to be included in statistical analysis for “cardiac damage.”49 Because none of the vitamin E studies had high Jadad scores or large sample sizes, statistically significant reductions in toxicities reported by the other 4 studies cannot be generalized for clinical use. Future studies should employ larger samples and better methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 26 clinical trials used glutathione or reduced glutathione (GSH) (2247), 11 used a type of vitamin E such as α -tocopherol or dl- α -tocopherol acetate (4859), 5 used N -acetylcysteine (NAC; 60–64), and others ( n = 10) used vitamin C, selenium, coenzyme Q10, zinc, or a combination of antioxidants (65–74; Table 1). Since GSH, vitamin E, and NAC were studied most frequently, we further analyzed the reports that examined these antioxidant supplements.…”
Section: Resultsmentioning
confidence: 99%
“…Strophanthin, the aglycone of which is strophanthidin, prevents doxorubicininduced alterations in isolated rabbit or dog hearts (57,58), digoxin inhibits the anthracycline-induced negative inotropic effects in paced cat hearts (58), and ouabain blocks anthracycline-induced depressant activity in isolated myocytes (59). The mechanism or mechanisms by which these agents operate remain controversial (1), but in clinical studies very little protection is observed (60)(61)(62)(63).…”
Section: Ohmentioning
confidence: 99%